Regulation of actin assembly by SCAR/WAVE proteins. (26th October 2005) - Ibarra, N.; Pollitt, A.; Insall, R.H.
Abstract : Actin reorganization is a tightly regulated process that co-ordinates complex cellular events, such as cell migration, chemotaxis, phagocytosis and adhesion, but the molecular mechanisms that underlie these processes are not well understood. SCAR (suppressor of cAMP receptor)/WAVE [WASP (Wiskott–Aldrich syndrome protein)-family verprolin homology protein] proteins are members of the conserved WASP family of cytoskeletal regulators, which play a critical role in actin dynamics by triggering Arp2/3 (actin-related protein 2/3)-dependent actin nucleation. SCAR/WAVEs are thought to be regulated by a pentameric complex which also contains Abi (Abl-interactor), Nap (Nck-associated protein), PIR121 (p53-inducible mRNA 121) and HSPC300 (haematopoietic stem progenitor cell 300), but the structural organization of the complex and the contribution of its individual components to the regulation of SCAR/WAVE function remain unclear. Additional features of SCAR/WAVE regulation are highlighted by the discovery of other interactors and distinct complexes. It is likely that the combinatorial assembly of different components of SCAR/WAVE complexes will prove to be vital for their roles at the centre of dynamic actin reorganization.